Primary Hip And Knee Arthroplasty At District Level Is Safe And May Reduce The Burden On Tertiary Care In A Low-Income Setting - Laubscher, Kim (Division of General Surgery, 2024)
Background: Arthroplasty procedures in low-income countries are mostly performed at tertiary centers, with waiting lists exceeding 12 to 24 months. Recently, this is further exacerbated by the impact of the Covid-19 Pandemic on elective surgeries. Providing arthroplasty services at other levels of healthcare aims to offset this burden, however there is a marked paucity of literature regarding surgical outcomes. This study aims to provide evidence on the safety of arthroplasty at district level. Methods: Retrospective review of consecutive hip and knee primary arthroplasty cases performed at a District Hospital (DH), and a Tertiary Academic Hospital (TH) in Cape Town, South Africa between 1st January 2015 and 31st December 2018. Patient demographics, hospital length of stay, surgery related readmissions, reoperations, post-operative complications, and mortality rates were compared between cohorts. Results: Seven hundred and ninety-five primary arthroplasty surgeries were performed at TH level and 228 at DH level. The average hospital stay was 5.2±2.0 days at DH level and 7.6±7.1 days for TH (p<0.05). Readmissions within 3 months post-surgery of 1.75% (4 patients) for district and 4.40% (35) for tertiary level (p<0.05). Reoperation rate of 1 in every 100 patients at the DH and 8.3 in every 100 patients at the TH (p<0.05) was noted. Death rate was 0.4% vs 0.6% at district and tertiary hospitals respectively (p>0.05). Periprosthetic joint infection (PJI) rate was 0.43% at DH and 2.26% at TH. The percentage of hip dislocation requiring revision was 0% at district and 0.37% at tertiary level. During the study period, 228 patients received their arthroplasty surgery at the DH; these patients would otherwise have remained on the TH waiting list. Conclusions: Hip and Knee Arthroplasty at District health care level is safe and; for the reason that the DH feeds into the TH; providing arthroplasty at district level may help ease the pressure on arthroplasty services at tertiary care facilities in a Southern African context. Adequately trained surgeons should be encouraged to perform these procedures in district hospitals provided there is appropriate patient selection and adherence to strict theatre operating procedures.